Impact of Using Social Media upon the Mental Health of Adolescent Students of preparatory Schools in Al-Diwanyah City - kareem, hassan; ali, eqbal (Iraqi National Journal of Nursing Specialties, 2017)
Objective: To know the impact of social networks on the mental health of adolescents in the city of Diwaniyah. Methodology: A descriptive cross-sectional study was conducted on adolescents in preparatory schools in ALDiwaniyah City Center, for the period from Jun 26, 2015 through to October 20, 2015. The schools were selected from using Probability sampling (240 random samples) six schools were selected from 32 schools (20 % from total number) the schools were chosen by writing the names of all schools on a pieces of paper and put in bags. Then, selected six schools random, three boys schools (2 preparatory and 1 secondary) three girls schools (2 preparatory and 1 secondary), then I chose the sample the students in grade (fourth preparatory and fifth preparatory) students (sample) were chosen at random to take 30%_33% of each grade. The data were collected through interview by questionnaire which consists of three parts, (1) socio-demographic characteristics of the sample consisted of four items, they includes students age, gender, social status, family economic status. (2) The programs and systems of social network (uses of networks and programs and the number of use hours). (3) Psychological aspect consists 13 items. Data analysis by using program of (SPSS) version 19, Descriptive data through determination of: Frequencies, Percentages, Mean of score, Graphical presentation and Statistical table, Inferential statistical data analysis by application Chi–square test used this test for determine the association between social network and adolescent’s mental health. Results: Facebook is most using of among Social network sites (42%) , as for systems electronic was greater using smart phones (mobile) (49.5%) , (53.8%) of the study subjects, (68.8%) of the study subjects, overall responses to the psychological health domain are high affected. Recommendations: The study recommended that Families or parent and teacher should employ a monitoring and frequent follow up for contain use addiction social networks sites, the mobile and others system that affect upon psychological health. Ministry of education should make more attention toward apply laws about inter the Mobil and other system to school. Organizations community health should be applying and reinforcing health education regard to the use of social networks sites